Design : the definitive visual history - Black, Alexandra; Grant, R. G., 1949-; Kay, Ann, 1959-; Wilkinson, Philip, 1955-; Zaczek, Iain (DK Publishing, 2015)
Design: The Definitive Visual History is a gorgeous visual celebration of design across the decades. Find out all about the major design movements of the last 150 years from Arts and Crafts to Bauhaus and browse through the beautiful image catalogs of everything from glassware to posters and typography to chairs. Arranged chronologically, from 1850 to the present day, follow the fascinating evolution of how design has influenced the look and functionality of the objects we use every day from telephones and cameras to toys, furniture and fashion. With profiles of iconic designers such as Alvar Aalto, Frank Gehry and Philippe Starck and stunning images of buildings and interiors, Design: The Definitive Visual History is a true celebration of classic design and the perfect package for design lovers
At head of title on cover: Smithsonian
Terminologický slovník
Keywords: design -- dějiny -- 19. století; design -- dějiny -- 20. století; průmyslový design -- dějiny -- 19. století; průmyslový design -- dějiny -- 20. století; dekorativní umění -- dějiny -- 19. století; dekorativní umění -- dějiny -- 20. století; design -- history -- 19th century -- history; design -- history -- 20th century -- history; industrial design -- history -- 19th century; industrial design -- history -- 20th century; decorative arts -- history -- 19th century; decorative arts -- history -- 20th century; obrazové publikace; pictorial works